A comparison of perimetric results with the Medmont and Humphrey perimeters - Landers, J; Sharma, A; Goldberg, I; Graham, S (British journal of ophthalmology, 2003)
Background: The Humphrey field analyser (HFA), Humphrey-Zeiss frequency doubling perimeter, and the Medmont automated perimeter (MAP) are three commonly used automated perimeters with threshold achromatic methodologies. Visual field loss may be detected earlier with strategies that target cell lines with reduced redundancy or which suffer selective damage. Method: To compare these three perimeters, 63 subjects who were glaucoma suspects, ocular hypertensives, glaucoma patients, or normal controls were recruited selectively. All subjects underwent testing using MAP central threshold, MAP flicker perimetry, HFA full threshold, HFA SITA perimetry, HFA short wavelength perimetry (SWAP), and frequency doubling perimetry (FDP). After visual field testing, equivalent tests were compared: MAP central threshold with HFA full threshold and HFA SITA perimetry; Medmont flicker perimetry with HFA SWAP and FDP. Results: On analysis of the MAP central threshold a kappa statistic and an area under the receiver operator curve (AUC) of 0.90 and 0.94, respectively, were found compared with HFA full threshold strategies, and 0.87 and 0.92 respectively, compared with HFA SITA. For MAP flicker a kappa statistic and an AUC of 0.65 and 0.81, respectively, were found compared with HFA SWAP and 0.87 and 0.96, respectively, compared with FDP. A quadrant analysis and comparison of mean defect between tests was also highly significant. Conclusion: Medmont and Humphrey perimeters correlated well; both may be used for clinical and research purposes with similar confidence.